2021
DOI: 10.4018/978-1-7998-7740-0.ch001
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Roles of Libraries and Librarians During and Post COVID-19 Pandemic

Abstract: This chapter highlights the challenges and opportunities that have and will arise as a result of the epidemic. When the spread of CoronaVirus 2019 (COVID-19) was announced by the World Health Organization (WHO), most schools, colleges, and tertiary institutes around the world were ordered to close so as to contain the spread. Currently, most learning institutions are experiencing challenges related to how to provide critical services; the most critical ones are linked to the library services. With the COVID-19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…The image that libraries had in the past as storage for books is no longer the case. According to Otike et al (2021), "the roles of librarians and information professionals have been challenged and questioned" (p. 11). Moreover, Otike et al (2021) assert that in the present digital era, there is a significant role of librarians and information professionals to help extract and find accurate and reliable information to the people in a friendly manner.…”
Section: Role Of Public Library and Library Development In Emerging C...mentioning
confidence: 99%
See 1 more Smart Citation
“…The image that libraries had in the past as storage for books is no longer the case. According to Otike et al (2021), "the roles of librarians and information professionals have been challenged and questioned" (p. 11). Moreover, Otike et al (2021) assert that in the present digital era, there is a significant role of librarians and information professionals to help extract and find accurate and reliable information to the people in a friendly manner.…”
Section: Role Of Public Library and Library Development In Emerging C...mentioning
confidence: 99%
“…According to Otike et al (2021), "the roles of librarians and information professionals have been challenged and questioned" (p. 11). Moreover, Otike et al (2021) assert that in the present digital era, there is a significant role of librarians and information professionals to help extract and find accurate and reliable information to the people in a friendly manner. The authors indicate that the role of libraries nowadays is to be able to "advocate the advancement of information literacy related to new technologies and media to help the users to independently detect the accuracy of information in the nearest future" (Otike et al, 2021, p. 12).…”
Section: Role Of Public Library and Library Development In Emerging C...mentioning
confidence: 99%
“…It's worth noting that the aforementioned surveys were conducted in the early months of the pandemic and reported on initial experiences. Most recent studies (see Leung et al, 2021 ; Otike et al, 2021 ) also reported user perceptions and roles of libraries and librarians in the post-epidemic era. However, the status of their patron services is in the process of dynamic changes, it is difficult to cover comprehensively, none have been carried out ranging from prior, during, and the normal COVID-19 pandemic.…”
Section: Literature Reviewmentioning
confidence: 99%
“…[…] Hence, libraries and librarians must move out of their comfort zones, and ensure they are with them." (Otike, Fredrick Wawire et al, 2021)…”
Section: Recommended Steps and Tasksmentioning
confidence: 99%